Simulation and analysis of the distributed photovoltaic generation systems based on DIgSILENT power factory - Majli Nema Hawas; Ihsan Jabbar Hasan; Mohannad Jabbar Mnati (Institute of Advanced Engineering and Science, 2022)
The voltage stability of the system has become an important component for the steady and dependable functioning of the power system as a result of multiple blackouts around the world (particularly in Iraq). Distributed photovoltaic systems are a subset of decentralized power generating systems that generate electricity using renewable energy sources like solar cells, wind turbines, and water power plants. In order to size a solar-grid-connected home system properly and to confirm the impact of photovoltaics on the system, this article will also do a steady-state analysis. The heating and cooling loads were taken into account when evaluating the residential load profile. With the help of predicted energy use, the photovoltaic (PV) system was sized. The solar system's power output was calculated, and the key variables affecting system performance were examined. The DigSilent power factory 15.2 was used to simulate all of the investigations. This article achieves better system stability outcomes.